(untitled) (World Bulletin of Social Sciences, 2022)
Ideas and technologies are transmitted through food and what results in the construction of social relations, as its nature seems to be of a cultural specificity that is not devoid of symbols indicative of deep morals and values in the social structure. Generation after generation invites the sharing of food and drink to produce social bonds recognized by hospitality, a symbolic identity that outweighs all the basic ideas of food and eating it.